FAMILY SUPPORT AND SELF-EFFICACY AS PREDICTORS OF RESILIENCE AMONG POSTPARTUM MOTHERS DURING ROLE TRANSITION - Umi Azizah Kusumaningrum (LPPM STIKES HUSADA JOMBANG, 2026)
Background: The postpartum period is a critical phase that demands complex adaptation to role changes as a mother. Resilience is an important factor in determining the ability of postpartum mothers to face the challenges of this transition period. Objectives: This study aimed to analyze the relationship between family support and self-efficacy with resilience of postpartum mothers in the working area of Tawangsari Health Center, Mojokerto Regency. Methods: A cross-sectional design was employed with 68 postpartum mothers selected using consecutive sampling. The instruments used were the Family Support Scale, General Self-Efficacy Scale, and Brief Resilience Scale. Data were analyzed using Pearson and Spearman correlation tests. Results: The majority of respondents had moderate family support (39.7%), moderate self-efficacy (44.1%), and low resilience (39.7%). There was a significant positive relationship between family support and resilience (r=0.447; p<0.001) and between self-efficacy and resilience (r=0.436; p<0.001), both with moderate correlation strength. Conclusion: Nursing interventions focused on strengthening family support and improving self-efficacy are needed to enhance postpartum mothers' resilience in facing role changes.